2001
DOI: 10.1046/j.1440-1746.2001.02456.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload impairs pro‐inflammatory cytokine responses by Kupffer cells

Abstract: Deposition of iron in Kupffer cells in chronic dietary iron overload results in an impaired pro-inflammatory cytokine response to lipopolysaccharide. Our observations may have relevance to the altered immune function observed in chronic iron-overload syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 52 publications
(59 reference statements)
2
24
0
Order By: Relevance
“…It is possible that secretion of a variety of cytokines by adipocytes and inflammatory macrophages may have modulated carcinogenesis after iron overload. 57 It also remains elusive whether mesothelioma truly originates from surface mesothelial cells, as mesothelial cells and lymphatic cells are seamlessly connected in the parietal pleura. 58 In expression microarrays, it is important to choose appropriate control samples.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that secretion of a variety of cytokines by adipocytes and inflammatory macrophages may have modulated carcinogenesis after iron overload. 57 It also remains elusive whether mesothelioma truly originates from surface mesothelial cells, as mesothelial cells and lymphatic cells are seamlessly connected in the parietal pleura. 58 In expression microarrays, it is important to choose appropriate control samples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, apoptosis, which can follow the mitochondrial swelling associated with permeability transition, is often accompanied by a transient increase in R123 fluorescence (38). Previous research has shown that iron deficiency and excess can also impair immune function (41,42) and neutrophil activation and metabolism (43,44). These findings strongly suggest that both iron deficiency and moderate excess are detrimental to mitochondria.…”
Section: Figmentioning
confidence: 99%
“…First, iron is known to affect cellmediated immune response (14). Excessive iron load in macrophages reduces their functions, including phagocytosis, respiratory burst, and cytokine expression (15)(16)(17), the effects likely mediated by iron-mediated toxicity (18). On the other hand, at non-toxic concentrations, iron promotes macrophage differentiation (19) and functions, including anti-microbial effects (20) and TNF-mediated cytotoxicity (21).…”
mentioning
confidence: 99%